THE INTERDEPENDENCE BETWEEN POVERTY AND HOMELESSNESS IN SOUTHEAST ASIA: THE CASE OF MALAYSIA, INDONESIA, THAILAND, AND SINGAPORE - Mohd Alif Jasni; Nazirah Hassan; Fauziah Ibrahim; Mohammad Rahim Kamaluddin, Norruzeyati Che Mohd Nasir, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Homelessness is a chronic issue in almost nearly every nation globally whether in underdeveloped, developing or advanced countries. In Southeast Asia, homelessness is rife due to various reasons, where poverty is notably one of the most prominent factors. This conceptual paper reviews past literature focusing on the issue of homelessness in selected countries in Southeast Asia namely, Malaysia, Indonesia, Singapore, and Thailand. The issue of poverty and homelessness has been a long-standing issue across the continent. The increase in homelessness due to poverty increases the challenge of reintegrating homeless individuals into society as most are denied the opportunity of permanent shelter. Living on the streets also implies that most of them are heavily dependent on support from both the government and society. This review of past literature reveals that homelessness and poverty are mutual, interdependent phenomenon that occurs simultaneously. All four countries (Malaysia, Indonesia, Thailand and Singapore) demonstrated that poverty is a significant trigger for the issue of homelessness, whereby most individuals are forced to live on the streets due to the vicious cycle of poverty. This review also significantly provides an overview on the issue of homelessness and poverty in the selected Southeast Asian countries, addressing the gap of limited research on the area of homelessness collectively in the region.